Detection of bovine leukemia virus RNA in blood samples of naturally infected dairy cattle - Alvarez, Irene; Porta, Natalia Gabriela; Trono, Karina Gabriela (MDPI, 2019)
The viral expression in vivo, in bovine leukemia virus (BLV)-infected cattle, is considered to be restricted to extremely low levels, and the mitosis of infected B lymphocytes is regarded as the main mode of virus persistence within the infected host. In this study, the presence of BLV RNA in whole blood from seven asymptomatic cows naturally infected with BLV during one year, including a complete milking cycle and two delivery time points, was investigated by nested-PCR using the oligonucleotides complementary to the tax and pol gene. BLV RNA was detected in four cows at different time points, especially in high blood proviral load cows and around delivery time. This study describes for the first time the detection of free BLV RNA in blood from BLV-infected asymptomatic cows. The results obtained suggest the occurrence of persistent low-level expression of the tax and pol genes that could be a result of viral reactivation, within the asymptomatic period. This finding may be important in the pathogenesis of BLV infection, associated with the delivery period.